Adult victims of domestic violence - battered women - Pagelow, M. D. (Journal of interpersonal violence, 1992)
This research update reviews the vast accumulation of literature on woman battering during the past decade to present a synopsis of some of the selected works that may offer the greatest assistance to activists, practitioners, and researchers in the field. Beginning with a brief look at some theoretical viewpoints, the report then reviews research on battered women and the medical field, law enforcement, the legal system, homicide, marital rape, and child custody. Summaries following each topic focus on changes brought about by research findings. The last section critically examines some popular myths and stereotypes, showing that research has largely failed to support them. These include the topics of psychopathology (of victims and/or offenders), dangerousness for police, the battered husband syndrome, mutual combat, and the cycle of violence. The conclusion suggests other common assumptions that call for critical examination and a few topics deserving greater research attention